2017
DOI: 10.1371/journal.pone.0188169
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits activation induced by urban particulate material or titanium dioxide nanoparticles in primary human endothelial cells

Abstract: Curcumin has protective effects against toxic agents and shows preventive properties for various diseases. Particulate material with an aerodynamic diameter of ≤10 μm (PM10) and titanium dioxide nanoparticles (TiO2-NPs) induce endothelial dysfunction and activation. We explored whether curcumin is able to attenuate different events related to endothelial activation. This includes adhesion, expression of adhesion molecules and oxidative stress induced by PM10 and TiO2-NPs. Human umbilical vein endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Montiel‐Dávalos et al reported that TiO 2 NPs induced adhesion molecules and the adhesion of monocytes onto HUVECs. Intracellular ROS was also induced, and inhibition of intracellular ROS by curcumin inhibited TiO 2 NP‐induced EC activation, indicating a role of oxidative stress (Montiel‐Dávalos et al, 2017). Interestingly, NM‐induced EC activation may be correlated with cytotoxicity.…”
Section: Adverse Vascular Effects Of Nmsmentioning
confidence: 99%
“…Montiel‐Dávalos et al reported that TiO 2 NPs induced adhesion molecules and the adhesion of monocytes onto HUVECs. Intracellular ROS was also induced, and inhibition of intracellular ROS by curcumin inhibited TiO 2 NP‐induced EC activation, indicating a role of oxidative stress (Montiel‐Dávalos et al, 2017). Interestingly, NM‐induced EC activation may be correlated with cytotoxicity.…”
Section: Adverse Vascular Effects Of Nmsmentioning
confidence: 99%
“…It has been reported that ZnO NPs and TiO 2 NPs can increase the secretion of adhesion molecules in HUVEC (C. M. Chen et al, 2020; Montiel‐Dávalos et al, 2017). Besides, decreased endothelial cells viability could lead to not only the loss of cell integrity but also increased vascular permeability, resulting in increased monocytes migration and adhesion (Bobryshev, 2006; M. T. Zhu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evidences showing that curcumin can decrease the level of TNF-α-induced VCAM-1 in vascular endothelial cells and the level of ICAM-1 in aneurysmal walls ( Huyut et al, 2022 ; Fan et al, 2019 ). Otherwise, ( Montiel-Dávalos et al, 2017 ) showed that air pollutants such as inhalable particles with an aerodynamic diameter of ≤10 μm (PM10) and titanium dioxide nanoparticles (TiO2-NPs) could induce the dysfunctions and abnormal activation of endothelial cells, which led to the over expressions of ICAM-1, VCAM-1, E-selectin and P-selectin, causing the excessive inflammatory cells infiltration and damage in the endothelial cells. And their results manifested that curcumin had an anti-inflammatory role by attenuating the dysfunctions and abnormal activation of endothelial cells by the exposures to PM10 and TiO2-NPs.…”
Section: Curcumin Suppresses the Over-activated Inflammationmentioning
confidence: 99%